Middle Meningeal Artery Embolization for Acute Epidural Hematomas: A Promising Alternative to Traditional Surgery - Stanishevskiy, Artem; Babichev, Konstantin; Abramyan, Arevik; Svistov, Dmitriy; Savello, Alexander; Martynov, Roman; Isaev, Djamalud (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Acute epidural hematoma (AEDH) is recognized as one of the most urgent neurosurgical conditions. Traditionally, the primary treatment for AEDH has involved craniotomy with surgical evacuation of the hematoma. However, with the widespread adoption of neurointerventional techniques, interest in their application to various forms of traumatic brain injuries has increased. Among these, embolization of the middle meningeal artery (MMA) has emerged as a minimally invasive treatment option for AEDH. This study evaluates the effectiveness of MMA embolization as a primary treatment for AEDH.We conducted a retrospective review of patients treated for AEDH with embolization of the MMA at our institution from January 2019 to July 2024. Patient demographics, clinical presentation, procedural details, and outcomes were analyzed.MMA embolization was successfully performed in 20 patients with AEDH, with only 2 cases requiring subsequent burr-hole evacuation. The thickness of the AEDH was 10 mm or more in 47.8% of cases, and a midline shift was observed in 65.2% of cases. The most common angiographic findings included arteriovenous fistulas (AVFs) and contrast extravasation. N-butyl cyanoacrylate was used as the embolic material in all cases. In one case, Squid 12 was added to enhance penetration at sites of extravasation. No patients experienced recurrent AEDH postintervention.MMA embolization is a promising minimally invasive treatment for AEDH, showing effectiveness as both a primary and adjuvant therapy. Future prospective multicenter studies are needed to validate preliminary findings and optimize treatment protocols for this high-risk patient population.
Keywords: traumatic brain injury; acute epidural hematoma; middle meningeal artery; embolization; arteriovenous fistula